Genesis a devotional commentary - Thomas, William Henry Griffith, 1861-1924; Gillespie, Winifred Griffith Thomas (Grand Rapids, MI Eerdmans, 1946)
Includes bibliographical references.
Chapter 50-69 held as a separate volume, which see also.
Keywords: Bible. O.T. Genesis -- commentaries